2021
DOI: 10.30773/pi.2020.0198
|View full text |Cite
|
Sign up to set email alerts
|

Persian Version of the Yale Food Addiction Scale 2.0: Psychometric Analysis and Setting Cutoff Point for the Food Cravings Questionnaire-Trait-Reduced

Abstract: Objective The aims of this study were to evaluate the psychometric properties of Persian translation of the Yale Food Addiction Scale 2.0 (YFAS 2.0) as a widely accepted questionnaire for the first time and to establish a cut off score for Food Craving Questionnaire-Trait-reduced (FCQ-T-r).Methods In this cross-sectional study, 330 visitors of family physician clinics in Shiraz, a city located in south of Iran, were selected. The English version of YFAS 2.0 was translated into Persian and used in this study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In particular, BMI, which was used in the original study (11), is often targeted to validate the construct of food addiction. The significant correlation between BMI and food addiction has been reported in previous studies (11,13,15,16,42,44,45), including the present one. Other validated measures such as those assessing binge eating (11-13, 16, 39) or food craving (42,44) are commonly used and are significantly correlated with scores on the YFAS 2.0.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In particular, BMI, which was used in the original study (11), is often targeted to validate the construct of food addiction. The significant correlation between BMI and food addiction has been reported in previous studies (11,13,15,16,42,44,45), including the present one. Other validated measures such as those assessing binge eating (11-13, 16, 39) or food craving (42,44) are commonly used and are significantly correlated with scores on the YFAS 2.0.…”
Section: Discussionsupporting
confidence: 87%
“…The significant correlation between BMI and food addiction has been reported in previous studies (11,13,15,16,42,44,45), including the present one. Other validated measures such as those assessing binge eating (11-13, 16, 39) or food craving (42,44) are commonly used and are significantly correlated with scores on the YFAS 2.0. Despite the aforementioned good properties, to the best of the present authors' knowledge, only three studies, including the present one, have reported testretest reliability for the YFAS 2.0 (14, 39).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Persian version of the YFAS 2.0 was used to assess FA (30). The YFAS 2.0 consists of 35 items that range from 0 (never) to 7 (every day) and are used to assess the DSM-5 substance-use disorder criteria, which have been applied to highly palatable foods [31].…”
Section: Methodsmentioning
confidence: 99%
“…The model contains more quantitative information and a continuous scale of measurement compared to a CTT approach and assumes that each individual has a fixed latent tendency along with each item with a particular fixed difficulty [25]. The Rasch model also will help assess the unidimensionality of both the YFAS 2.0 and mYFAS 2.0, and both instruments have been found to be unidimensional [20,[26][27][28][29][30][31][32][33][34][35][36][37][38]. Moreover, both the YFAS 2.0 and mYFAS 2.0 were expected to create a single factor structure of FA to differentiate between those with or without FA [18,19].…”
Section: Introductionmentioning
confidence: 99%